Qualifications of ministers: a comparative study between Malaysia, India, Singapore and United States / Mohamad Fadhly Mohd Zamry, Iylia Hakim Abdul Wahid and Ahmad Zamir Zamri - Mohd Zamry, Mohamad Fadhly; Abdul Wahid, Iylia Hakim; Zamri, Ahmad Zamir (2012)
"Qualifications of Ministers: A Comparative Study between Malaysia, India, Singapore and United States", is a legal study on the legal criteria regarding the qualification a person should have before being appointed as a member of the Executive branch of the government, in countries like India, Singapore and the United States of America. Qualifications which are envisaged legally in those countries, India, Singapore and the United States of America, are to be compared with the legal qualification which a person should have in Malaysia, before being appointed as a Minister. Qualifications set forth in the countries mentioned, are compared with that of Malaysia, to improve the competency of the ministers in Malaysia. It is to ensure that, only candidates with an impressively qualified background are to be appointed as Ministers. This is to ensure that only competent people will be at the helm of guiding Malaysia through the process of nation building. Apart from ensuring that only competent candidates are appointed to guide Malaysia through the process of nation building, such legal qualification of appointment is to ensure that the needs of the people in Malaysia can be effectively served only by competent Ministers.